Clinical significance of non-culprit plaque regression following acute coronary syndrome: A serial intravascular ultrasound study. Issue 2 (August 2019) - Endo, Hirohisa; Dohi, Tomotaka; Miyauchi, Katsumi; Kuramitsu, Shoichi; Kato, Yoshiteru; Okai, Iwao; Yokoyama, Miho; Yokoyama, Takayuki; Ando, Kenji; Okazaki, Shinya; Shimada, Kazunori; Suwa, Satoru; et al.
Highlights: This research aimed to investigate the impact of plaque change in patients with acute coronary syndrome. Patients who achieved plaque regression by intravascular ultrasound had lower rates of clinical events. Plaque regression with on-treatment low levels of low-density lipoprotein cholesterol was an only better predictor of major adverse cardiac and cerebrovascular events. Abstract: Background: The use of serial intravascular ultrasound (IVUS) for coronary atherosclerosis has offered valuable insight into plaque regression (PR) or progression. However, the beneficial effects of PR on the long-term clinical outcomes in patients with acute coronary syndrome (ACS) remain unclear. We aimed to evaluate the impact of coronary plaque change in patients following primary percutaneous coronary intervention. Methods: We retrospectively analyzed data from 4 prospective clinical trials involving 173 patients with ACS who underwent serial IVUS of non-culprit lesions on statin treatment at baseline and at 6 or 8 months of follow-up. The relationship of the IVUS findings with the change in percent atheroma volume (PAV), on-treatment low-density lipoprotein cholesterol (LDL-C), and major adverse cardiac and cerebrovascular events (MACCE) were investigated. Results: In our serial IVUS analysis, baseline plaque volume and PAV were 79.6 mm 3 and 46.0%, respectively. The overall change in PAV was −1.5% [interquartile range (IQR): −4.1% to 1.0%], and PR (i.e. PAV change from baseline <0) was observed in 67.1% of patients. They were followed up observationally for a mean of 3.5 years and a total of 37 MACCE occurred. The rate of MACCE tended to be lower in patients with PR than in those without PR (18.1% vs. 28.7%, p = 0.14). A multivariate Cox hazard model analysis demonstrated that achievement of both PR and on-treatment low LDL-C levels (<70 mg/dL) was the only significant independent predictor of MACCE (hazard ratio: 0.42, 95% confidence interval: 0.19–0.88; p = 0.02). Conclusions: Achievement of both PR and sufficient lowering of the LDL-C was clinically important in post-ACS management.